2016
DOI: 10.1098/rsif.2016.0355
|View full text |Cite
|
Sign up to set email alerts
|

Controlled cobalt doping in the spinel structure of magnetosome magnetite: new evidences from element- and site-specific X-ray magnetic circular dichroism analyses

Abstract: ResearchCite this article: Li J et al. 2016 Controlled cobalt doping in the spinel structure of magnetosome magnetite: new evidences from element-and site-specific X-ray magnetic circular dichroism analyses. J. R. Soc. The biomineralization of magnetite nanocrystals (called magnetosomes) by magnetotactic bacteria (MTB) has attracted intense interest in biology, geology and materials science due to the precise morphology of the particles, the chain-like assembly and their unique magnetic properties. Great effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 52 publications
3
44
1
Order By: Relevance
“…Note that, according to EDS (see the supplementary information), the Co content in the magnetosomes is only 1.6% at./Fe, thus the Co ferrite in the magnetosomes is not stoichiometric ( Co 0.05 Fe 2.95 O 4 ). In spite of the low Co content, it has been previously reported that the magnetic properties of Co-magnetosomes change notably with respect to the undoped ones [20][21][22] .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Note that, according to EDS (see the supplementary information), the Co content in the magnetosomes is only 1.6% at./Fe, thus the Co ferrite in the magnetosomes is not stoichiometric ( Co 0.05 Fe 2.95 O 4 ). In spite of the low Co content, it has been previously reported that the magnetic properties of Co-magnetosomes change notably with respect to the undoped ones [20][21][22] .…”
Section: Resultsmentioning
confidence: 97%
“…Note that, according to EDS (see the supplementary information), the Co content in the magnetosomes is only 1.6% at./Fe, thus the Co ferrite in the magnetosomes is not stoichiometric ( ). In spite of the low Co content, it has been previously reported that the magnetic properties of Co-magnetosomes change notably with respect to the undoped ones 20 22 . Mn The control bacteria show a well defined Mn K-edge XANES spectrum, suggesting that Mn is an abundant element in the cell in basal conditions (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We have also studied the impact of minimal growth media on magnetosome composition. Whereas, we increased magnetosome iron relative purity by reducing the concentration of other metals than iron in the growth media, i.e., the concentration of iron relatively to other analyzed metals in magnetosomes increases from 93.8% using non-minimal growth media (Zhang et al, 2011) to 99.8% using minimal growth media, previous studies have reported a faculty of MTB to incorporate other metals than iron, such as Co, Zn or Ni, in magnetosomes by growing MTB in media enriched with these metals (Staniland et al, 2008;Kundu et al, 2009;Li et al, 2016). Another interesting observation lies in the rate of metal incorporation, which seems to depend on the type of metal that is considered.…”
Section: Discussionmentioning
confidence: 99%
“…This task was not won in advance. Indeed, some of the metals that we needed to eliminate like cobalt have been reported to be necessary for biosynthesis of the B12 vitamin and in some key enzymes responsible for magnetosome formation in AMB-1 strain (Li et al, 2016). Furthermore, according to previous reports, other metals like copper, manganese and zinc, could be essential since they are agents acting as cofactors of bacterial antioxidant defense enzymes (Agranoff and Sanjeev, 1998), thus preventing oxidative stress in bacteria and modifying magnetosomes characteristics (Popa and Fang, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is supposed that transition metal ions doped in magnetosomes are in the +2 oxidation state and occupy some Fe 2+ octahedral sites in the Fe 3 O 4 inverse spinel structure. It was in fact recently clarified that Fe 2+ ions were replaced by Co 2+ at the octahedral sites of magnetosome magnetite [ 16 ]. It was also demonstrated that Magnetospirillum species incorporate copper and manganese into magnetosomes, as a result of which the magnetic properties of magnetite particles alter [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%